Assessment of Measured and Calculated Dose Rate of Co-60 Teletherapy Machine: 06 Years’ Experience at NORIN Nawabshah, Pakistan - Muhammad Waqar; Touqir Ahmad Afridi; Quratulain Soomro; Muhammad Shahban (Journal of Physics and Its Applications, 2022)
It is essential to determine the absolute output dose of Co-60 source in the radiation treatment periodically. It is because overdosage may cause radiation hazards whereas under dosage may lead to the unsatisfactory treatment of cancer. The current study is focused on the consistency of monthly dose output verification of the cobalt-60 Teletherapy unit which should be within ±2% as per international standards. In the present study, the measured and calculated dose rate of the Co-60 teletherapy unit at Nuclear Medicine Oncology and Radiotherapy Institute Nawabshah (NORIN) for the last 6 years is analyzed. The dose measurement was done in water phantom 30×30×30 cm3 at 80 cm Source to Surface Distance with 5cm depth by using calibrated electrometer and PTW ionization chamber. The measured output dose rate obtained by actual dosimetry is within ±2% of the dose rate calculated by the decay method and the deviation lies within the permissible limit as prescribed by International Atomic Energy Agency (IAEA), International Commission on Radiological Units and Measurement (ICRUM)and American Association of Physicists in Medicine (AAPM). The variation in measurements obtained is within the tolerable limits according to standard protocols and codes. Thus, our study shows a homogenous trend in the dose rate of the Co-60 teletherapy machine.